A feasibility study of perioperative vitamin D supplementation in patients undergoing colorectal cancer resection - Vaughan-Shaw, P. G.; Buijs, L. F.; Blackmur, J. P.; Ewing, A.; Becher, H.; Theodoratou, E.; Ooi, L. Y.; Din, F. V. N.; Farrington, S. M.; Dunlop, M. G. (Frontiers in Nutrition, 2023)
Background Vitamin D supplementation improves colorectal cancer (CRC) survival outcomes in randomized trials. The aim of this study was to test the feasibility, safety and efficacy of vitamin D supplementation in the pre- and perioperative period in patients undergoing CRC surgery. Methods Patients were given 3200IU oral cholecalciferol (D3) per day perioperatively. Serial serum 25-hydroxyvitamin (25OHD) was measured by liquid chromatography tandem mass spectrometry and compared to untreated CRC controls. 25OHD and C-reactive protein (CRP) levels were compared using adjusted generalized linear mixed-effects models. Results A total of 122 patients underwent serial perioperative sampling, including 41 patients given high-dose perioperative supplementation. Supplementation was well-tolerated with no adverse or serious adverse events related to supplementation reported. Pre-operative supplementation increased 25OHD levels on the day of surgery (103.9 vs. 42.5 nmol/l, P = 8.2E–12). Supplementation increased 25OHD levels at all post-operative timepoints (P < 0.001) and attenuated the post-operative drop in 25OHD (46 vs. 24% drop, P = 3.0E–4). Rate of vitamin D peri-operative insufficiency was significantly less in those on supplementation (e.g., day 3–5, 14 vs. 84%, P = 1.41E–08), with multivariate modeling across all timepoints indicating a ∼59 nmol/l higher 25OHD compared to control patients (P = 3.7E–21). Post-operative CRP was lower in patients taking supplementation (e.g., day 3–5 timepoint; 129 vs. 81 mg/l, P = 0.04). Conclusion High dose pre-operative vitamin D supplementation is associated with higher perioperative 25OHD levels, lower rates of vitamin D insufficiency and reduced early post-operative CRP. Alongside published evidence for a beneficial effect of vitamin D on CRC survival outcomes, these novel findings provide strong rationale for early initiation of vitamin D supplementation after a diagnosis of CRC.